152k views
1 vote
I have to drag the answers in the correct orders

I have to drag the answers in the correct orders-example-1
User Nonsleepr
by
5.0k points

1 Answer

0 votes

Greetings!

As the equation is
5(x-y) + 2y = 5 , first thing we need to do is multiply out the brackets:


5x - 5y +2y = 5

Which then simplifies to:


5x - 3y = 5

Now we can rearrange the formula to:


5x = 3y + 5

Now we need to divide the 3y + 5 by 5:


(3y + 5)/(5) Which results in the end result being:


x = (3)/(5)y = 1


Which means, in top to bottom the order is: 4,3,2,1,5


Hope this helps!

User Nubbel
by
5.8k points